Assessing the acceptability of biometrics in HIV prevention programme by Hillbrow sex workers - Nyamhuno, Shepherd (My University, 2019)
Sex workers face several challenges in Hillbrow which include the risks of HIV and STI infection, stigma and discrimination in public health facilities, arrests and exploitation from the police as well as violence from the clients. Sex workers do not always bring their identity documents to the clinic and they are frequently changing their names thereby creating many multiple accounts for an individual. The biometrics have the potential to solve the problems of unique identifiers for Esselen Street Clinic. This study undertook to find out if the biometrics were acceptable to the sex workers. A mixed-methods approach made up of questionnaires, focus group discussions and in-depth interviews for employees was employed. A sample of 120 questionnaires found out that 64.6% accepted the biometrics when used at Esselen Street Clinic. Moreover, 79% had a positive perception of biometrics. The focus group discussion showed that although the sex workers trusted the clinic staff, they had problems with fear of the unknown including someone hacking the system and the data ending up in the hand of future prospective employees. Sex workers also cited that they were using biometrics in other platforms such as the Department of Home Affairs, banks and SASSA. This gave them the confidence to accept them if they were to be placed at the clinic. In order to understand the acceptance of the biometrics by the sex workers, in-depth interviews with employees were carried out. It emerged from the in-depth interviews with the staff members that the clinic had invested much in tailor-made services, which are very convenient for sex workers. Moreover, the continual capacity building in sex worker sensitisation and the quality improvement programme has yielded better outcomes and quality services that are attractive to sex workers. The non-judgemental attitudes of the employees gave the sex workers confidence to accept the biometrics. It was interesting to note that migrant sex workers were more sceptical and fearful of biometrics than local ones due to illegal immigrant status and experience of harassment at the hands of the police. The study concluded that a sex worker-friendly clinic, like Esselen Street Clinic, could perhaps have a better acceptance rate than a public health facility would. With intense lobbying and education, there are higher chances of getting an even higher acceptance rate of the biometrics.
Thesis presented in partial fulfilment for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, 2019